Macroeconomic policy trilemma in open economies: which policy option is ideally suited to the Malaysian context? - A. Mansur M. Masih, (Penerbit Universiti Kebangsaan Malaysia, 2005)
Right now Malaysia has the major economic fundamentals more or less right(excepting the budget deficit). The inflation rate is low (1.2%), unemployment rate is relatively low (3.5%), current account balance is significantly positive (13.7%), foreign reserves are growing and comfortable and the savings rate is high. Given Malaysia’s current economic and political strength and the experiences of many other open economies, it appears to me that as long as the macroeconomic discipline as well as the ongoing financial and corporate sector restructuring developments are maintained, Malaysia can enhance its FDI inflows, growth rate of output and employment significantly by continuing with the current independent monetary policy but shifting towards a managed peg linked to a basket of currencies weighted by trade balance along with an accelerated removal of capital controls. The regime change will send a powerful positive signal to the outside world about Malaysia’s own confidence in its future prospects